2001
DOI: 10.1143/jjap.40.5664
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Dielectric Properties of Solid Solutions of Pb(Yb1/2Nb1/2)O3–PbTiO3 with a High Curie Temperature near a Morphotropic Phase Boundary

Abstract: The Pb(Yb1/2Nb1/2)O3–PbTiO3 (PYN–PT) binary system single crystal near the morphotropic phase boundary (MPB) composition with (100) planes of 1–2 mm length on one side was successfully grown by the flux method using PbO–PbF2–B2O3 flux. The PYN–PT (47/53) single crystal was found, by simultaneous microdifferential thermal analysis and thermogravimetric analysis, to show a peritectic melting point at 1205°C with a decomposition of the perovskite crystals into a pyrochlore phase and a liquidus point at 1253°C. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…The segregation coefficient of Ti 4? is smaller than unity, which is similar to that of the PMN-PT crystals [1,21] and other systems [17,19,23].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The segregation coefficient of Ti 4? is smaller than unity, which is similar to that of the PMN-PT crystals [1,21] and other systems [17,19,23].…”
Section: Resultssupporting
confidence: 81%
“…Therefore, it is extremely urgent to develop new crystals with both high piezoelectric properties and high phase transition temperatures. In the past decade, many binary solid solutions were investigated, such as Pb(Sc 1/2 Nb 1/2 )O 3 -PbTiO 3 (PSN-PT) [7][8][9][10][11][12][13][14], Pb(In 1/2 Nb 1/2 )O 3 -PbTiO 3 (PIN-PT) [15,16], Pb(Lu 1/2 Nb 1/2 )O 3 -PbTiO 3 (PLN-PT) [17], and Pb(Yb 1/2 Nb 1/2 )O 3 -PbTiO 3 (PYN-PT) [18,19], among which Pb(Sc 1/2 Nb 1/2 )O 3 -PbTiO 3 (PSN-PT) exhibits peculiar electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some piezoelectric SCs with high T c have been studied in recent years in order to overcome the above-mentioned disadvantages. The dielectric and piezoelectric properties of PInNT and PYbNT SCs with T c > 250 • C were reported by Yasuda's and Shrout's groups [6,7]. Eitel and coworkers reported a new series of piezoelectric materials, (1-x)BiScO 3 -xPbTiO 3 , with high T c [8].…”
Section: Piezoelectric Single Crystals With High T C and T Rtmentioning
confidence: 80%
“…Therefore, the thermal stability and voltageproof nature of the electric properties are insufficient for some applications, such as medical transducers. Recently, some piezoelectric SCs with high T c have been studied in order to overcome the above-mentioned disadvantages [4][5][6][7][8].…”
mentioning
confidence: 99%
“…Therefore, over the past few years, tremendous efforts have been made to improve the temperature stability of the properties, two potential approaches have been adopted so far: shifting T c /T rt to higher temperature by composition tuning, and taking advantage of the engineered domain configuration in single crystals. 3 In the first method, through elements substituting and/or adding of other end-members, numerous new higher T c /T rt binary and ternary material systems were developed, including Pb(In 1/2 Nb 1/2 )-PbTiO 3 (PIN-PT), 6,7 Pb(Yb 1/2 Nb 1/2 )-PbTiO 3 (PYN-PT), 8,9 Pb(Sc 1/2 Nb 1/2 )-PbTiO 3 (PSN-PT), 10 Pb(In 1/2 Nb 1/2 )-Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PIN-PMN-PT), [11][12][13][14][15] Pb(Mg 1/3 Nb 2/3 )O 3 -PbZrO 3 -PbTiO 3 (PMN-PZ-PT), [16][17][18][19] and Pb(Sc 1/2 Nb 1/2 )-Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 (PSN-PMN-PT), 20 etc. However, it was found that the temperature stability remained unsolved despite of the high T c /T rt .…”
mentioning
confidence: 99%